"Make live, let die" in the age of governmentality. About the actuality and importance of the Foucauldian approach of biopolitics - López, Cristina (Revista de Filosofía, 2017)
Foucault’s researches on biopolitics were object of a wide receipt between well-knows authors. But, in spite of taking them as an inspiration for his own analyses, this did not prevent them from raising critiques so severe that it force to indagate which is the contribution of the approach of the French thinker. In this article, I will try to refute these objections and to prove that his contribution consisted of associating the conformation of the biopower with the appearance of the liberal and neoliberal gubernamentalities thus showing the impact on the life and the death exercised by both frames of political rationality.